2015
DOI: 10.1016/j.microrel.2015.08.018
|View full text |Cite
|
Sign up to set email alerts
|

The surface energies of β-Sn — A new concept for corrosion and whisker mitigation

Abstract: Corrosion data provided under high-temperature and high-humidity conditions as well as tin whisker growth studies are explained by differences in the surface energy of lattice planes within the crystal structure of β-tin. For this purpose, electrodeposited tin finishes were investigated regarding their microstructure utilizing X-ray diffraction, cross-sectional SEM and EBSD analysis. The corrosion as well as the tin whisker propensity strongly depends on the preferred orientation of the surface finishes. With … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Jagtap et al [17] reported that whisker growth is more likely from the Sn grains with lower indices, like <100> or near-<100>, than from higher ones, like <321>. Eckold et al [18] showed similar results, that the <211> orientation is a preferred orientation because this orientation ensures lower corrosion propensity than the <220> or <321>. Zhang et al [19] reported that whisker susceptibility is generally low in Sn layers with multi-peak texture (like <112> <101> <103>).…”
Section: Introductionmentioning
confidence: 99%
“…Jagtap et al [17] reported that whisker growth is more likely from the Sn grains with lower indices, like <100> or near-<100>, than from higher ones, like <321>. Eckold et al [18] showed similar results, that the <211> orientation is a preferred orientation because this orientation ensures lower corrosion propensity than the <220> or <321>. Zhang et al [19] reported that whisker susceptibility is generally low in Sn layers with multi-peak texture (like <112> <101> <103>).…”
Section: Introductionmentioning
confidence: 99%
“…Eckold et. al found that in Sn layers the preferred orientation of grains is <211>, because grains with such orientation have lower corrosion and tin whisker susceptibility than grains with <321> or <220> orientation [17]. However, Zhang et.…”
mentioning
confidence: 99%
“…Although this two-stage sodiation process was observed in all three different diffusion couples, a slight difference is observed at the very beginning of the reaction; the first-stage Na diffusion, as characterized by the amorphization of c-Sn, is slower for the Na/Sn⟨101⟩ diffusion couple. This is probably because of the comparatively stable nature of the (101) surface of the Na/Sn⟨101⟩ diffusion couple. , However, after this initial amorphization stage, the amorphous structures of the interfaces become similar regardless of the orientation of c-Sn; this weakens/nullifies the directionality of Na diffusion and promotes isotropic diffusion, explaining the mechanistic origin of isotropic swelling (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…This is probably because of the comparatively stable nature of the (101) surface of the Na/Sn⟨101⟩ diffusion couple. 54,55 However, after this initial amorphization stage, the amorphous structures of the interfaces become similar regardless of the orientation of c-Sn; this weakens/nullifies the directionality of Na diffusion and promotes isotropic diffusion, explaining the mechanistic origin of isotropic swelling (Figure 2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%